Social Programs and Formal Employment : Evidence from the Brazilian Bolsa Familia Program - Fruttero, Anna (IMF Working Papers; Working Paper ;, 2020)
Employment is key to combating poverty. Thus, detractors of social assistance programs argue that they create disincentives to work. While there is substantial evidence showing limited effects of these programs on overall labor supply, the jury is still out with respect to their impact on formal employment. This paper exploits an unannounced change in the eligibility rule of the Bolsa Familia program in Brazil, one of the oldest and largest conditional cash transfers in the world, to identify the causal impact of the program on formal employment, combining three large administrative datasets. This paper finds that the program has a positive effect on entry in formal labor market, especially for younger cohorts.